Գրիգոր Լուսավորչի կերպարի մարմնավորումը գեղանկարչության մեջ - Ստեփանյան, Աշոտ («Զանգակ - 97»)
Gregory IHuminator is one of the greatest and supreme names of the Armenian people, who at the beginning of the 4lh Century will introduce the ideas of religion and will State it as State religion. The life and work of Gregory Illuminator have bccome the bases for varios scientific work and his immaculate image thoroughly came into the religious culture, assuming versatile interpretation in painting, drawing, metal-working, pottery, engraving, embroidery, etching, and in the spheres of applied arts.
Keywords: Արվեստ; Գեղանկարչություն; Պատմություն